Neurogliaform and Ivy Cells: A Major Family of nNOS Expressing GABAergic Neurons - Armstrong, Caren; Krook-Magnuson, Esther; Soltesz, Ivan (Frontiers in Neural Circuits, 2012)
Neurogliaform and Ivy cells are members of an abundant class of neuronal nitric oxide synthase (nNOS) expressing GABAergic interneurons found in diverse brain regions. These cells have a defining dense local axonal plexus, and display unique synaptic properties, including a biphasic postsynaptic response with both a slow GABAA component, and a GABAB component, following even a single action potential. The type of transmission displayed by these cells has been termed ‘volume transmission,’ distinct from both tonic and classical synaptic transmission. Electrical connections are also notable in that, unlike other classes, neurogliaform family cells will form gap junctions not only with other neurogliaform cells, but also with members of other GABAergic cell classes. In this review we focus on neurogliaform and Ivy cells throughout the hippocampal formation, where recent studies highlight their role in feedforward inhibition, uncover their ability to display a phenomenon called persistent firing, and reveal their modulation by opioids. The unique properties of this class of cells, their abundance, rich connectivity, and modulation by clinically relevant drugs make them an attractive target for future studies in vivo during different behavioral and pharmacological conditions.